Unilateral synostosis of the zygomaticotemporal suture associated with mandibular coronoid process impingement in a dog - Ryan, J. M.; Fraga-Manteiga, E.; Schwarz, T.; Clements, D. N. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
A 13-month-old dog was investigated for the complaint of open-mouth locked jaw. There were not any previous episodes of trauma witnessed. Computed tomographic evaluation revealed unilateral zygomaticotemporal synostosis and associated craniofacial asymmetry, with impingement of the mandibular coronoid process resulting in unilateral temporomandibular joint subluxation. Closed reduction of the subluxation was not maintained. Partial zygomaticotemporal suturectomy resulted in resolution of the clinical signs. To the author's knowledge, isolated zygomaticotemporal synostosis with associated temporomandibular subluxation has not been reported in the dog.
Keywords: Zygomaticotemporal; suture; synostosis; dog; temporomandibular